Severe Preeclampsia and Anemia in Pregnancy: Risk Factors, Prevention, and Management – Case Report - Abitmer Gultom; Nur Nunu Prihantini; Beatrix Melanie Beding (GLOBAL HEALTH SCIENCE GROUP, 2025)
Severe preeclampsia (PE) and anemia are two common medical conditions during pregnancy that have serious impacts on maternal and fetal health. Preeclampsia is a new-onset hypertensive disorder (≥140/90 mmHg) after 20 weeks of gestation, which may be accompanied by proteinuria and organ dysfunction in the mother or uteroplacental dysfunction. If left untreated, preeclampsia can progress to eclampsia, characterized by seizures, neurological disturbances, and anincreased risk of vital organ complications, including kidney failure, pulmonary edema, and liver dysfunction. To report a case of Severe Preeclampsia and Anemia in a 29-year-old female patient. The subject was a 29-year-old G2P1A0 woman in her final trimester of pregnancy who came with the chief complaint of tightness in the abdomen, cramp-like pain, headache, and blurred vision. The patient previously had a history of uncomplicated pregnancy. A 29-year-old G2P1A0 woman presented with complaints of abdominal tightening, cramping, headache, and blurred vision, who was subsequently diagnosed with severe preeclampsia and anemia. Findings included Anemia, Leukocytosis, and Proteinuria are Present. the patient was hospitalized, underwent a caesarean section, and received appropriate medical management.